A new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the French and Swiss Jura Mountains - Reding, Jean-Paul G.; Bolard, Audrey; Vinçon, Gilles (Zootaxa, 2017)
A new species of Protonemura Kempny, 1898, P. jurassica sp. n., endemic to the Jura Mountains of France and Switzerland, is described from both adults and nymphs. Information on the distribution, ecological preferences and conservation status of this new species is also provided.